Optical Properties of Organic Beetroot Dye and its Different Applications - AL_Shaikh Hussin, suma H (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
Extraction and preparation of red organic dye from beetroot plant in different concentrations by using the solvent extraction process. Ethanol was the solvent used to prepare five different concentrations at the ratio of (Dye: Ethanol) abbreviated (D: E) 5:0,4:1, 3:2, 2:3,1:4. The optical, structural, and morphological properties are studied for the samples. The results appeared using the UV-Vis spectroscope the maximum peak of absorption (A) spectrum at wavelength Aλmax=480 nm when the transmittance (T) at the same wavelength 25% and the reflectivity 0.8%. Florescent (F) spectrum of beetroot dye is measured at wavelength Fλmax=535nm achieved to redshift about Δλ=55 nm. Also, measured the energy band gap Eg=2.36 eV and the refractive index n=1.36 of beetroot dye. Finally, the atomic force microscopy (AFM) found the average particle size of dye is 85.9 nm. The results illustrated the organic beetroot dye has a good homogeneity and stability at room temperature so that it can be used in painting, optical, and industrial applications. Also, the dye can be applied in color optics and color optical contact lenses, LASER, and sensitive dye solar cells, which means in different applications because it was harmless, environmentally friendly, and fall under green energy.